1987
DOI: 10.1093/mutage/2.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the dominant lethal effects of acrylonitrile and acrylamide in male Fischer 344 rats

Abstract: Acrylonitrile (ACN) and acrylamide (AA), structurally similar vinyl monomers, are both animal carcinogens. ACN is weakly mutagenic in bacteria and induces sister-chromatid exchange, unscheduled DNA synthesis and cell transformation in cells in culture. AA induces chromosomal aberrations in bone marrow, blood and germ cells in vivo, and dominant lethal mutations in the germ cells of male mice and rats. In the current study, the ability of AA and ACN to induce dominant lethal mutations in the germ cells of male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Based upon the concordance of tumour sites between AA and GA, it can be concluded that carcinogenic activity of AA is due to its metabolic conversion to GA. (2012). These previous evaluations referred to several studies reporting on the reproductive and developmental toxicity of orally administered AA Sakamoto and Hashimoto, 1986;Smith et al, 1986;Working et al, 1987;Sublet et al, 1989;Chapin et al, 1995;Tyl et al, 2000a,b). AA did not significantly affect mating performance in female rats, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the concordance of tumour sites between AA and GA, it can be concluded that carcinogenic activity of AA is due to its metabolic conversion to GA. (2012). These previous evaluations referred to several studies reporting on the reproductive and developmental toxicity of orally administered AA Sakamoto and Hashimoto, 1986;Smith et al, 1986;Working et al, 1987;Sublet et al, 1989;Chapin et al, 1995;Tyl et al, 2000a,b). AA did not significantly affect mating performance in female rats, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A lower frequency of pregnant females obtained after exposure of spermatozoa to AA and X-rays + AA [14] can be compared to a higher frequency of sperm head abnormalities, because malformed spermatozoa are not able to fertilize. Also, the results of other AA studies suggest that the late spermatids and spermatozoa are the most susceptible to damage [13,15,17,[44][45][46] . In previous studies, a significant increase in micronucleus frequency in bone marrow was observed 24 h after treatment with 50-100 mg/kg bw of AA [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have found positive effects in micronucleus tests in spermatids of rodents [9][10][11][12]. AA causes dominant lethal mutations in mice [8,[13][14][15] and in rats [16,17], and produces increases in malformed sperm heads [18].…”
Section: Introductionmentioning
confidence: 99%
“…Leonard et al (1981) 68) reported that AN had negative results in both micronucleus test using murine erythrocytes and dominant lethal test using germs cells from male mice. Working et al (1987) 69) also showed in dominant lethal test that oral administration to rats at dose levels up to 60 mg/ kg/day resulted in negative results.…”
Section: Mutagenicitymentioning
confidence: 99%